2010
DOI: 10.1055/s-0030-1250461
|View full text |Cite
|
Sign up to set email alerts
|

Application of Proteomic and Bioinformatic Techniques for Studying the Hepatoprotective Effect of Dioscin against CCl4-induced Liver Damage in Mice

Abstract: In this study, the significant hepatoprotective effect of dioscin against CCl₄-induced acute liver damage in mice was first discovered, and the effect produced by dioscin at the dose of 100 mg/kg was equal to the action produced by silymarin at the dose of 200 mg/kg. Then, 1-dimension gel electrophoresis was used to separate the liver proteins, and five differentially expressed bands were selected. After in-gel digestion, 71 proteins were identified by nano-RP-HPLC-ESI-MS/MS/MS. Further network analysis sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Pharmacological investigations have demonstrated that dioscin possesses antiinflammatory, lipid-lowering and anti-cancer activities (Kaskiw et al, 2009;Lu, Yin, Xu, & Peng, 2011;Sautour, Mitaine-Offer, Miyamoto, Dongmo, & Lacaille-Dubois, 2004). Our previous investigations have shown that dioscin is highly effective against chemical-induced liver injury, non-alcoholic fatty liver disease, alcohol-induced liver injury and carbon tetrachloride (CCl 4)-induced liver fibrosis Xu T. T. et al, 2014;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological investigations have demonstrated that dioscin possesses antiinflammatory, lipid-lowering and anti-cancer activities (Kaskiw et al, 2009;Lu, Yin, Xu, & Peng, 2011;Sautour, Mitaine-Offer, Miyamoto, Dongmo, & Lacaille-Dubois, 2004). Our previous investigations have shown that dioscin is highly effective against chemical-induced liver injury, non-alcoholic fatty liver disease, alcohol-induced liver injury and carbon tetrachloride (CCl 4)-induced liver fibrosis Xu T. T. et al, 2014;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dioscin, a spirostane saponin with antihepatitis activity (Lu et al, 2011), accumulates in the liver after intravenous or oral administration at a concentration much higher than dioscin in plasma and other tissues (Li et al, 2005). The value of hepatic clearance (CL in situ, predicted = 0.83 6 0.10 ml/min/kg) is 21.5% of plasma clearance (3.86 6 0.51 ml/min/kg) (Li et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, di-ao-xin-xue-kang capsules prepared from D. nipponica Makino have been used for more than 10 years in China to treat coronary heart disease (Liu et al, 2004b). The bioactivity of dioscin (diosgenyl 2,4-di-O-a-L-rhamnopyranosyl-p-D-glucopyranoside), a major component of di-ao-xin-xue-kang capsules, has been reported and includes antihepatitis (induced by carbon tetrachloride) (Lu et al, 2011), antitumor (Mi et al, 2002;Liu et al, 2004a;Hu et al, 2012), and antifungal (Sautour et al, 2004) activity. Dioscin ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmarcological studies have showed that dioscin has anti-tumor, anti-hyperlipidemic, anti-fungal and anti-virus activities [15-18]. And our previous studies showed that dioscin has significant hepatoprotective effects on carbon tetrachloride (CCl 4 ) and acetaminophen induced liver damage in mice [19-21]. In the future, more and more researches of dioscin will be investigated because of its important medical value.…”
Section: Introductionmentioning
confidence: 99%